Low-lying states of 92, 93Nb excited in the reactions induced by the weakly-bound nucleus 6Li near the Coulomb barrier *Supported by National Natural Science Foundation of China (U1867210, 11775098, 11475013, U1832130 and 11775316). (October 2019) - Lv 吕, Yi-Feng 翌丰; Lu 陆, Jing-Bin 景彬; Zhang 张, Gao-Long 高龙; Wu 吴, Yi-Heng 义恒; Yuan 袁, Cen-Xi 岑溪; Fu 傅, Guan-Jian 冠健; Zhang 张, Guang-Xin 广鑫; Huang 黄, Zhen 珍; Wang 王, Ming-Li 明李; Hu 胡, Shi-Peng 世鹏; Sun 孙, Hui-Bin 慧斌; Zhang 张, Huan-Qiao 焕乔; et al.
Abstract: Excited states of odd-odd nucleus 92 Nb and odd-A nucleus 93 Nb were populated in the 6 Li+ 89 Y reaction with an incident energy of 34 MeV. The processes that produce 92, 93 Nb and can be measured by a combination of light charged particle and gamma ray measurements are discussed. Twenty new transitions are observed and eight new levels are constructed in 92 Nb, and in addition two new transitions are added to the level scheme of 93 Nb. Using shell model calculations, the low-lying structure of 92 Nb is investigated and compared with the experimental results.